2022
DOI: 10.3389/fgene.2022.851390
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Chromobox Family Members as Potential Prognostic Biomarkers and Therapeutic Targets for Human Esophageal Cancer

Abstract: Background: Chromobox family proteins (CBXs) are vital components of epigenetic regulation complexes and transcriptionally inhibit target genes by modifying the chromatin. Accumulating evidence indicates that CBXs are involved in the initiation and progression of multiple malignancies. However, the expression, function, and clinical relevance such as the prognostic and diagnostic values of different CBXs in esophageal carcinoma (ESCA) are still unclear.Methods: We applied Oncomine, TCGA, GEO, GEPIA, UALCAN, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In this study, we found that USP15 was highly expressed in breast cancer by searching the TCGA databases [ 32 , 54 ]. Then by searching the bioinformatics database UALCAN, GEPAI, Kaplan-Meier we.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that USP15 was highly expressed in breast cancer by searching the TCGA databases [ 32 , 54 ]. Then by searching the bioinformatics database UALCAN, GEPAI, Kaplan-Meier we.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is well-established that the epigenetic dysregulation accelerates tumorigenesis, and at least partially, facilitates cancer stemness. Several reports suggest, that CBX family members possess the potential to become druggable targets in distinct tumor types, including breast, lung, ovarian, esophageal, and colon cancer [ 11 , 66 , 67 , 68 , 69 ]. However, these reports do not raise the question of therapeutic targeting of the stem cell-like phenotype of solid tumors and do not prove the engagement of CBX family members in molecular mechanism modulating cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal tissues or paracancerous tissues, the expression of all or some of the CBX1/2/3/4/5/8 members is upregulated in most cancer tissues, including glioma (67-69), tongue squamous cell carcinoma (TSCC) (70), head and neck squamous cell carcinoma (HNSCC) (71), breast cancer (BC) (15,(72)(73)(74)(75)(76)(77)(78)(79)(80), non-small cell lung cancer (NSCLC) (81)(82)(83)(84)(85), esophageal cancer (EC) (86)(87)(88)(89)(90), gastric cancer (GC) (91)(92)(93)(94)(95)(96)(97)(98), pancreatic adenocarcinoma (PAAD) (99,100), colorectal cancer (CRC) (101-104), urinary bladder cancer (UBC) (105), sarcoma (106) and osteosarcoma (107,108). As a tumor suppressor, CBX7 is expressed at low levels in most tumors, such as glioma, HNSCC (71), EC (87,88), GC (93)(94)(95)(96)(97)(98), PAAD (109), CRC (103,104), clear cell renal cell carcinoma (ccRCC) …”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 99%
“…CBX3 is a poor prognostic factor in as many as 13 tumor types (67,69-71,80 ,81,84,86-88,101,106,110,111,114,116,122,123). CBX4 is of prognostic value in BC (76,80), LUAD (85), EC (86)(87)(88), GC (92,94,95,98), HCC (11) and ccRCC (110). In addition, patients with BC (80), LUAD (84), GC (94)(95)(96)(97)(98), CRC (103), sarcoma (106), SKCM (113) with upregulated CBX5 and HNSCC (71) and ccRCC (110) with downregulated CBX5 have poor prognosis.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation